Long-term risk of carotid restenosis in patients randomised to endovascular treatment or endarterectomy in the Carotid and Vertebral Artery Transluminal Angioplasty Study (CAVATAS): long-term follow up of a randomised trial - MC CABE, DOMINICK (My University, 2009)
Background In the Carotid and Vertebral Artery Transluminal Angioplasty Study (CAVATAS), early recurrent carotid stenosis was more common in patients assigned to endovascular treatment than it was in patients assigned to endarterectomy (CEA), raising concerns about the long-term effectiveness of endovascular treatment. We aimed to investigate the long-term risks of restenosis in patients included in CAVATAS. Methods 413 patients who were randomly assigned in CAVATAS and completed treatment for carotid stenosis (200 patients had endovascular treatment and 213 patients had endarterectomy) had prospective clinical follow-up at a median of 5 years and carotid duplex ultrasound at a median of 4 years. We investigated the cumulative long-term incidence of carotid restenosis after endovascular treatment and endarterectomy, the effect of the use of stents on restenosis after endovascular treatment, risk factors for the development of restenosis, and the effect of carotid restenosis on the risk of recurrent cerebrovascular events. Analysis was by intention to treat. This study is registered, number ISRCTN01425573. Findings Severe carotid restenosis (?70%) or occlusion occurred significantly more often in patients in the endovascular arm than in patients in the endarterectomy arm (adjusted hazard ratio [HR] 3?17, 95% CI 1?89?5?32; p<0?0001). The estimated 5-year incidence of restenosis was 30?7% in the endovascular arm and 10?5% in the endarterectomy arm. Patients in the endovascular arm who were treated with a stent (n=50) had a significantly lower risk of developing restenosis of 70% or greater compared with those treated with balloon angioplasty alone (n=145; HR 0?43, 0?19?0?97; p=0?04). Current smoking or a history of smoking was a predictor of restenosis of 70% or more (2?32, 1?19?4?54; p=0?01) and the early finding of moderate stenosis (50?69%) up to 60 days after treatment was associated with the risk of progression to restenosis of 70% or more (3?76, 1?88?7?52; p=0?0002). The composite endpoint of ipsilateral non-perioperative stroke or transient ischaemic attack occurred more often in patients in whom restenosis of 70% or more was diagnosed in the first year after treatment compared with patients without restenosis of 70% or more (5-year incidence 23% vs 11%; HR 2?18, 1?04?4?54; p=0?04), but the increase in ipsilateral stroke alone was not significant (10% vs 5%; 1?67, 0?54?5?11). Interpretation Restenosis is about three times more common after endovascular treatment than after endarterectomy and is associated with recurrent ipsilateral cerebrovascular symptoms; however, the risk of recurrent ipsilateral stroke is low. Further data are required from on-going trials of stenting versus endarterectomy to ascertain whether long-term ultrasound follow-up is necessary after carotid revascularisation. Funding British Heart Foundation; UK National Health Service Management Executive; UK Stroke Association.
PUBLISHED
Keywords: Stroke